Tool use, or not tool use, that is the question: is the necessity hypothesis really inconsequential for the African great apes? - Masi, Shelly (Frontiers in Mammal Science, 2023)
Investigating the drivers of tool use in animals has recently received great attention because of its implication in understanding animals’ cognition and the evolution of tool use in hominins. The necessity hypothesis posits tool use as a necessary response to food scarcity, but its role is an ongoing debate. The largest body of literature comparing animal tool use frequencies is with regard to primates, particularly comparisons between the Pan species. This supports the hypothesis that tool use is rarer in wild bonobos because of differential manipulation abilities of chimpanzees rather than different ecological needs. In this article, I aim to enrich the discussion concerning the necessity hypothesis and the ecological drivers of tool use in apes. The higher feeding flexibility of bonobos may be a key aspect to explaining the lower use of feeding tools than that observed in chimpanzees. The diet flexibility of bonobos is similar to that of the lowest level of tool users among the wild great apes: the gorilla. Gorillas can thus help to shed further light on this debate. When fruit is scarce, Western gorillas and bonobos rely more on widely available proteinaceous herbs than chimpanzees, who remain highly frugivorous. Chimpanzees may thus face a greater necessity to search for an alternative to obtain high-quality food: tool-assisted feeding. An indirect piece of evidence for this higher level of herbivory is that the prevalence of gut ciliates in bonobos is double that of chimpanzees. In each animal species, a different combination of necessity, opportunities, predisposition, and learning processes are likely to be at play in the emergence of flexible tool use in animals.